A MATHEMATICAL MODEL TO STUDY THE IMPACT OF IRRESPONSIBLE INFECTIVE IMMIGRANTS AND VERTICAL TRANSMISSION ON THE DYNAMICS OF HIV/AIDS. (2015) - CHINWENDU, E.; NWAOKOLO, NWAOKOLO; MARTINS, A.; GWERYINA, GWERYINA; REUBEN, I.
No abstract available